The Importance of Physical Fitness Programs for Firefighters - AL Busafi, Majid (Journal of Physical Education, 2021)
Physical fitness is a major factor affecting firefighters’ ability to perform under harsh circumstances. This study aimed to investigate the importance of considering a physical fitness program for firefighters and determine whether such a program should be mandated to create a safe and efficient work environment. A survey was conducted to observe the existing fitness program impacts on firefighters’ fitness level, their satisfaction with the program, and their opinion upon mandating the program. The study showed that firefighters’ fitness levels differed significantly depending on whether the firefighters were subjected to a fitness program or not. The majority (73%) of the respondents support mandating a physical fitness program and encouraged such a program to be included in a school degree plan. However, more than half of the participants (57%), evaluated their fitness program as inaccurate. Hence, fitness program components must be thoroughly structured to enhance the program competency. Recommendations from the respondents were focused on facilitating Civil Defense Centers with gyms, proper gymnastic equipment, and professional trainers.